THE EFFECT OF BOILED WATER OF THE RED BETEL LEAF TO REDUCING THE SYMPTOMS OF PATHOLOGICAL FLOUR ALBUS IN ADOLESCENTS IN MODERN BOARDING SCHOOLS IN KUTA BARO, THE DISTRICT OF ACEH BESAR - isra, zarifa; Santy, Putri; Novemi, Novemi (Journal of Midwifery and Community Health (JMCH), 2023)
Background: Flour albus is a problem that is often encountered in adolescents. Female students who studied at modern Islamic boarding schools also complained about the same problem. Not maintaining personal hygiene and lack of knowledge is the main cause of flour albus in students. Handling flour albus can be done non-pharmacologically through the provision of red betel boiled water. Method: This study uses a quasi-experiment method with a pretest-posttest control group design. The study involved 30 young women who experienced pathological flour albus. Respondents came from two different Islamic boarding schools. Fifteen young women from Islamic Boarding School Daruzzahidin were given treatment and 15 from Islamic Boarding School Darul Hikmah for the control group. Treatment by giving 100 ml of decoction of red betel dau to wash away the genitals. This treatment is carried out for 14 days. The sampling technique uses purposive sampling, according to the criteria set by the researcher. Result: There were differences before and after the use of red betel boiled water and no differences before and after observation in the control group. Pretest results in the treatment group showed the incidence of pathological discharge in the moderate category of as many as 7 people (46.7%). For posttest results, the whitish category changed, where young women who were initially in the moderate category became whitish in the mild category, namely 9 people (60%). Conclusion: There is an influence of the administration of boiled water of red betel on the incidence of pathological discharge. It is hoped that policymakers will be able to increase adolescent knowledge about personal hygiene and non-pharmacological treatment to overcome flour albus.